2008
DOI: 10.1002/jhm.352
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a physician assistant/hospitalist service in an academic medical center: Impact on efficiency and patient outcomes

Abstract: BACKGROUND:Accreditation Council on Graduate Medical Education (ACGME) duty hour restrictions have led to the widespread implementation of non–house staff services in academic medical centers, yet little is known about the quality and efficiency of patient care on such services.OBJECTIVE:To evaluate the quality and efficiency of patient care on a physician assistant/hospitalist service compared with that of traditional house staff services.DESIGN:Retrospective cohort study.SETTING:Inpatient general medicine se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 13 publications
6
94
2
Order By: Relevance
“…Patients admitted with a principal diagnosis of congestive heart failure to our intervention team had a significantly lower 30-day readmission compared to patients with the same diagnosis on standard housestaff teams. 4 Whereas some studies have found that hospitalist and traditional housestaff services have similar efficiency and costs of care, 18 others have found that hospitalist care is associated with lower costs, especially as hospitalists gain experience on the job. 19 These cost offsets may facilitate implementation and sustainability, even without philanthropic support.…”
Section: Discussionmentioning
confidence: 99%
“…Patients admitted with a principal diagnosis of congestive heart failure to our intervention team had a significantly lower 30-day readmission compared to patients with the same diagnosis on standard housestaff teams. 4 Whereas some studies have found that hospitalist and traditional housestaff services have similar efficiency and costs of care, 18 others have found that hospitalist care is associated with lower costs, especially as hospitalists gain experience on the job. 19 These cost offsets may facilitate implementation and sustainability, even without philanthropic support.…”
Section: Discussionmentioning
confidence: 99%
“…At present hospitalists on staffs reach 50,000 physicians, more than cardiologists, in almost all medical centers in US [9][10][11][12]. The advantages of HOS include a more rapid, effective and precise dealing with problems no matter in diagnoses, prescription of medications, therapeutic strategies or the communications with patients by sharing decision making with attending physicians rather than by residency in advance [13,14]. Several studies have reported that HOS model at wards provides shorter length of stay and improves quality of care [11,[14][15][16].…”
Section: Application Of Integrated Medicalmentioning
confidence: 99%
“…68 MLWs have also been shown to provide safe and effective abortion and anaesthetic services. [69][70][71] There a re data to indicate that MLWs are an effi cient as well as effective investment. Surgery by MLWs in Mozambique produced the same outcome as doctors whose training cost ten times that of the técnicos de cirugía.…”
Section: Quality Of Carementioning
confidence: 99%